Dimensi-Dimensi Pembelajaran Bahasa - Siskawati Ziliwu; Meilyani Meilyani; Desi Rismayani Sinaga; Wiryo Sastro Handoyo (Jurnal Multidisiplin Dehasen (MUDE), 2022)
This article examines the dimensions of language learning in high grade MI (Madrasah Ibtidaiyah) children. Learning dimensions are an instructional framework that is comprehensive in nature to assist educators in planning learning experiences that will be presented to their students. inquiry, exploration, and problem investigation, students will be encouraged to learn through problem solving, both individually and in groups. The method used in this research is to explore studies related to this article, either in the form of research results or studies in other forms. The results of this article show an increase in the quality and language skills of high grade MI children through the implementation of the language learning dimensions model. This quality improvement makes educators and students productive, creative and accomplished..